2020
DOI: 10.1108/ijppm-07-2019-0323
|View full text |Cite
|
Sign up to set email alerts
|

Examining occupational stress, job satisfaction and gender difference among bank tellers: evidence from Ghana

Abstract: PurposeBank tellers have been ignored in stress research. The purpose of this paper is to investigate the relationships between occupational stress, job satisfaction, and gender difference among bank tellers in Ghana.Design/methodology/approachUsing a cross-sectional survey approach, the authors used questionnaires to collect data from bank tellers in Ghana. Valid questionnaires were retrieved from 112 tellers across four banks. The hypotheses were tested using Pearson r-test, standard multiple regression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 55 publications
3
28
0
2
Order By: Relevance
“…These results support that older employees tend to be engaged more with their work than younger employees, and highly educated employees tend to hold higher personal resources than less educated employees. However, even though we were expecting controls, such as gender, to have a differential impact on work burnout and work engagement, it seems that this study supports findings of Dartey-Baah et al (2020), who showed that gender is not a strong differentiating predictor of such constructs.…”
Section: Resultssupporting
confidence: 62%
“…These results support that older employees tend to be engaged more with their work than younger employees, and highly educated employees tend to hold higher personal resources than less educated employees. However, even though we were expecting controls, such as gender, to have a differential impact on work burnout and work engagement, it seems that this study supports findings of Dartey-Baah et al (2020), who showed that gender is not a strong differentiating predictor of such constructs.…”
Section: Resultssupporting
confidence: 62%
“…Education and job satisfaction had no significant relationship in study of Thilagaraj (2018). In Ghana, gender had no significant relationship with the job satisfaction among bank tellers (Dartey-Baah et al. , 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 89%
“…Gender was also investigated in relation to the job satisfaction. In Ghana, gender had no significant relationship with the job satisfaction among bank tellers (Dartey-Baah et al, 2020). Same was confirmed by Toker (2011) that not only gender but also marital status had no significant relationship to the job satisfaction among the academicians of the universities of Turkey.…”
Section: Job Satisfaction In Telecommunications Industrymentioning
confidence: 87%
See 1 more Smart Citation
“…The bank management, along with the human resources department, could utilize burnout intervention strategies concentrated on changing the organization (Organizational-level intervention) (Lubbadeh, 2020), which focuses on reducing the mismatch between the employees and the organization (e.g., overload, fairness, role ambiguity) and stressor at the workplace, or individual-level strategies that improve the employees' ability to manage and cope with the workplace stressor. For example, strategies geared towards developing the employees' psychological capital (PsyCap) and emotional intelligence can provide the employees with the necessary skills to cope with work stress and abilities to effectively manage their emotions and behaviors (Dartey-baah et al, 2020). Human resource managers in banks should also perform and design practical training and coaching procedures to promote employees' mental and physical health; in addition, organizing more out of work activities (e.g., sporting events, annual party) to increase the employee's feelings of belonging to the organization.…”
Section: Discussionmentioning
confidence: 99%